Edge effect factor affecting the tribological properties in water of protrusion surface textures on stainless steel. Issue 2 (6th June 2018) - Wu, Xingyang; Ge, Zhou; Niu, Haozhi; Ruan, Jingjie; Zhang, Jianhua
Abstract : Surface textures have been demonstrated to have a positive effect on the friction reduction. However, sharp edges of the normally textured patterns usually cause stress concentration and severe wear during sliding, especially for non‐conformal contacting pairs. In this study, protrusion‐type textures were fabricated at different area ratios on stainless steel discs and edge profiling was performed for the protrusions, and friction tests were conducted in water to investigate the tribological properties. The results show that the friction was reduced markedly by edge profiling due to the formation of wedge contact and improvement of lubricant supply to the contact interfaces under low load. Under high load, severe wear destroyed the wedge contact resulting in high friction as those of the normally textured pairs. High area ratio exhibited better friction reduction effect. The stress analysis via ANSYS indicated that much high stress concentrated at the edges of the protrusions and could be reduced significantly by edge profiling.